La tartamudez en el cine: análisis textual del cambio de paradigma en su representación - Dr. Guillermo MEJÍAS MARTÍNEZ,Dr. Marta MANGADO (Fonseca, Journal of Communication, 2023)
The image that the seventh art provides regarding disability is fundamental for its collective perception. This paper stud-ies, in the form of textual analysis, two films that address stuttering and whose productions are twenty-two years apart: A Fish Called Wanda (Charles Crichton, 1988) and The King’s Speech (Tom Hooper, 2010). Both productions are funda-mental to understand how, in the last decades, the representation of the collective of people who stutter in cinema has changed.